Health literacy of hearing-impaired adolescents, barriers and misunderstandings they encounter, and their expectations - GÜR, KAMER; TURAN, SULTAN (ELSEVIER SCIENCE INC, 2020)
Background: Adults who are deaf or hard of hearing (D/HoH) have lower levels of health literacy compared to their counterparts who can hear. It is unclear, however, whether or not this inequality manifests in adolescence. Objective or hypothesis: This study aims to determine levels of health literacy among D/HoH adolescents and to identify barriers and misunderstandings they encounter as well as their expectations when applying for healthcare services. Methods: This descriptive study was conducted with 88 D/HoH adolescents over the age of 15. The Health Sciences Faculty granted approval for the study. Results: Of the adolescents, 70.5% had inadequate, 19.3% had limited, 2.3% had adequate and 8% had excellent health literacy levels. Those who had difficulty in communicating with the doctor (25%), those who misused the prescribed medication (13.6%) and those who could not use the medication without help (43.2%) had low THLS scores (<0.05). Those who stated that they did not understand what the nurses said (43.2%) or the health education materials (56.8%) and had significantly low THLS scores (<0.05). Of these adolescents, 55.7% expected their prescriptions or care procedures to be given to them in writing, and 87.5% expected that these would be explained to them in sign language. A significant relationship was observed between hearing disability and health literacy (R = 0.659, R2 = 0.434) (p < 0.01). Conclusion: Most D/HoH adolescents have a significantly lower level of health literacy, which is more likely linked with poor communication and misunderstandings concerning medication instructions. (C) 2020 Elsevier Inc. All rights reserved.
Keywords: Deaf and hard-of-hearing adolescents; Health literacy; Expectations Barriers and misunderstandings; Healthcare services; DEAF ADULTS; CARE; COMMUNICATION; PEOPLE; PERCEPTIONS; ACCESS; INDIVIDUALS; COMMUNITY; KNOWLEDGE; SERVICES